Analisis Hukum dan Etika terhadap Tanggung Jawab PERS di Masyarakat Indonesia - Ritonga, Rohani; Sari, Yulia Indah Permata; Sitompul, Qory Amalia Az-Zahra; Maruhawa, Tamara Khaisya; Putri, Rizky Amanda; Efendi, Erwan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The text discusses the rules and ethics of journalism, focusing on guiding individuals or groups in managing the behavior of the press, broadcasting, and mass media from the process of news gathering, writing, composition, and dissemination. The research methodology used in this study is Systematic Literature Review (SLR) to determine the most appropriate method. The research applies three stages: planning, implementation, and analysis of the results, which analyze the results of the Literature Review conducted by the author. Based on the research results and discussions regarding the analysis of Indonesian press law and ethics in being accountable for press coverage that can trigger conflicts in society, it can be concluded that reporting that can trigger conflicts in society is through the right of reply (Article 5 paragraph [2] Press Law) and the right of correction (Article 5 paragraph [3] Press Law).